Optimization of laboratory procedures for intrauterine insemination: survey of methods in relation to clinical outcome. (29th June 2018) - Lemmens, L.; Kos, S.; Beijer, C.; Braat, D. D. M.; Jonker, M. A.; Nelen, W. L. D. M.; Wetzels, A. M. M.
Abstract: Background: There is a wide practice variation of used methods and outcomes in IUI in fertility laboratories. Standardization of the IUI procedure is important for reducing inconsistency among laboratories in counseling infertile couples and in pregnancy results. The aim of the study was to evaluate the currently used laboratory procedures of IUI in Dutch fertility laboratories and their effect on IUI pregnancy results. Additionally, the methods for semen analysis (SA) were evaluated, as SA is related to IUI in terms of inseminated sperm number and IUI counseling. Material and Methods: This questionnaire survey study was sent to laboratories participating in the Dutch external quality control program for semen analysis (SKML) and consisted of 46 questions concerning laboratory management, methods for semen analysis and IUI, and clinical results. The results were analyzed using univariable and multivariable logistic regression models. Results: A total of 52 laboratories (out of 99) provided information on used methodologies for SA or laboratory procedures of IUI and the organization of the laboratory. A wide variability was confirmed in used methods for both SA and IUI. Evaluation of pregnancy results obtained during 3 years (2013‐2015) showed that specific used laboratory methods have a significant effect on the probability of becoming pregnant. Discussion and conclusion: Important to remark is that in this survey study cycle‐specific data, including variables of the individual couples (age, stimulation protocol, etc), were not included and may have effects on the results. The reported results provide an overview of the current practice performance; however, the organization of fertility laboratories is changing rapidly. The use of standardized methods in IUI is important for optimizing the performance of care and improving pregnancy results. The knowledge on used procedures, however, is limited, and further research on factors involving SA and the IUI procedure is necessary.